Metabolic Engineering for Enhanced Medium Chain Omega Hydroxy Fatty Acid Production in Escherichia coli - Xiao, Kang; Yue, Xiu-Hong; Chen, Wen-Chao; Zhou, Xue-Rong; Wang, Lian; Xu, Lin; Huang, Feng-Hong; Wan, Xia (Frontiers in Microbiology, 2018)
Medium chain hydroxy fatty acids (HFAs) at ω-1, 2 or 3 positions (ω-1/2/3) are rare in nature but are attractive due to their potential applications in industry. They can be metabolically engineered in Escherichia coli, however, the current yield is low. In this study, metabolic engineering with P450BM3 monooxygenase was applied to regulate both the chain length and sub-terminal position of HFA products in E. coli, leading to increased yield. Five acyl-acyl carrier protein thioesterases from plant and bacteria were first evaluated for regulating the chain length of fatty acids. Co-expression of the selected thioesterase gene CcFatB1 with a fatty acid metabolism regulator fadR and monooxygenase P450BM3 boosted the production of HFAs especially ω-3-OH-C14:1, in both the wild type and fadD deficient strain. Supplementing renewable glycerol to reduce the usage of glucose as a carbon source further increased the HFAs production to 144 mg/L, representing the highest titer of such HFAs obtained in E. coli under the comparable conditions. This study illustrated an improved metabolic strategy for medium chain ω-1/2/3 HFAs production in E. coli. In addition, the produced HFAs were mostly secreted into culture media, which eased its recovery.